2012
DOI: 10.1037/a0028540
|View full text |Cite
|
Sign up to set email alerts
|

Examining social justice attitudes among play therapists: Implications for multicultural supervision and training.

Abstract: This article reports the findings of a survey that investigated social justice attitudes among play therapists (N = 448) and its relation to multicultural supervision and multicultural education. Descriptive statistics and a Pearson correlations test were used to analyze results. Results indicated that social justice attitude was positively correlated to the number of continuing education credits, the percentage of time both receiving and providing supervision with a multicultural focus, the quality of supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
5
25
0
Order By: Relevance
“…It is suggested that with the appropriate materials and support, CCPT can aid in developing internal strength and resolution resulting in better adjustment, coping, and buffering in dealing with social justice issues such as poverty and racism (Baggerly & Parker, 2005;Bondy et al, 2007;Ceballos et al, 2012;Landreth, 1993). This is vital as experiences with racism and negative judgments from adults in authority can lead to levels of mistrust that could hamper the sense of positive support and relationship building (Spencer, Jordan, & Sazama, 2004).…”
Section: Cultural Effectiveness Of Ccptmentioning
confidence: 98%
See 4 more Smart Citations
“…It is suggested that with the appropriate materials and support, CCPT can aid in developing internal strength and resolution resulting in better adjustment, coping, and buffering in dealing with social justice issues such as poverty and racism (Baggerly & Parker, 2005;Bondy et al, 2007;Ceballos et al, 2012;Landreth, 1993). This is vital as experiences with racism and negative judgments from adults in authority can lead to levels of mistrust that could hamper the sense of positive support and relationship building (Spencer, Jordan, & Sazama, 2004).…”
Section: Cultural Effectiveness Of Ccptmentioning
confidence: 98%
“…It is the goal of the CCPT therapist that children will enhance communication through symbolically acting out feelings, thoughts, and experiences not able to be expressed in words resulting in improvement through vicarious experiences gained from the play sessions (Bratton et al, 2005;Fall, Balvanz, & Johnson, 1999;Van Velsor, 2009). Further, the multicultural components of a child's life are open for free exploration through a sensitivity to cultural diversity and the ability to develop skills within the context of cultural realities and history (Ceballos et al, 2012;Garrett & Herring, 2001, Landreth et al, 2009Lee, 2001). By allowing children to express themselves in their own culturally accepted ways (e.g., through the use of specific songs and dances, culturally appropriate pretend foods, observance of cultural rituals, or the use of language and storytelling), counselors can add to their understanding and ultimately their effectiveness as professionals, resulting in a better ability to help others to possess their own identities and create new possibilities (Gladding, 1997;Landreth et al, 2009).…”
Section: Ccpt and Culturementioning
confidence: 98%
See 3 more Smart Citations